High-quality chalcogenide glass waveguide fabrication by hot melt smoothing and micro-trench filling. (31st March 2016) - Zhai, Yanfen; Qi, Renduo; Yuan, Chenzhi; Zhang, Wei; Huang, Yidong
Abstract: We propose a fabrication method for chalcogenide glass (ChG) waveguides based on hot melt smoothing and micro-trench filling. ChGs has low melting points and good flowability. Experiments show that this method can realize high quality As2 S7 glass waveguides with reverse ridge structures. The attenuations of the fundamental quasi-TE mode and quasi-TM mode are 0.1 and 0.9 dB/cm, respectively. This method avoids fabrication processes, such as photolithography, lift-off, and dry or wet etching that are directly applied to the ChG films. It provides a simple way to fabricate high quality ChG waveguides, which have great potential for applications in integrated nonlinear optical devices.